Vertical Transmission of Hepatitis B Virus-An Update (2023)
ABSTRACT: Hepatitis B virus (HBV) infection is a major public health problem in the world. Approximately 296 million people are chronically infected. In endemic areas, vertical transmission is a common route of transmission. There are several strategies for the prevention of HBV vertical transmission, such as antiviral treatment during the third trimester of pregnancy and immunoprophylaxis to newborns that includes the administration of hepatitis B immune globulin (HBIG) and an HBV vaccine. Despite this, immunoprophylaxis failure can occur in up to 30% of infants born to HBeAg-positive mothers and/or with high viral load. Therefore, management and prevention of HBV vertical transmission is of paramount significance. In this article, we provided a review of the epidemiology, mechanisms of pathogenesis and risk factors of vertical transmission, as well as the strategies implemented to prevent the infection.